ANALISIS MOTIVASI KERJA PADA GURU SD IT AZ ZUHRA PUSAT KOTA PEKANBARU - Irawan, Dika (Komunitas Manajemen Kompetitif, 2025)
This research Motivation is the driving force behind a series of human behavioral processes aimed at achieving goals. The elements of motivation include arousing, directing, maintaining, demonstrating intensity, being persistent, and having a purpose. In this study, the authors present field findings regarding factors related to work motivation among teachers at the Az Zuhra Islamic Elementary School Center. These factors are internal factors, including: the desire to survive, job satisfaction, the desire for appreciation, and recognition. External factors include: work environment, adequate compensation, good supervision, job security, and status and responsibility.